Українська витинанка кін. ХХ – поч.ХХІ ст.: тема, історіографія наукового дослідження - Грищенко, О. (Інститут народознавства НАН України, 2007)
In the article are considered actual needs of research-work on Ukrainian paper-cuts of last decades as well as aim and tasks of studies in this artifacts. Light is thrown upon publications by authors as S.Ivasechko, H.Kulchenko, H.Mishchenko, S.Tinadaichuk, A.Shevchuk and others. The importance of papercuts in contemporary artistic process is stated.